2019
DOI: 10.1021/acs.jpclett.9b02543
|View full text |Cite
|
Sign up to set email alerts
|

VLS Homoepitaxy of Lead Iodide Nanowires for Hybrid Perovskite Conversion

Abstract: Controlled fabrication of lead halide-based perovskite (LHP) nanostructures provides a new methodology for exploiting the excellent optoelectronic properties of the material. Here, we report the vapor–liquid–solid (VLS) growth of a highly uniform and dense array of [0001]-oriented PbI2 nanowires using PbI2 thin film as the epitaxial substrate layer. We show that reducing the lattice mismatch of the van der Waals epitaxial PbI2 substrate layer is necessary to accommodate the aligned nanowire growth. Our propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Thus, the difference in the degree of perovskite conversion between type A and B might be related to the accessibility of gaseous MAI onto the surface of nanowire sidewalls, necessitating the evaluation of MAI affinity to the exposed PbI 2 surface facets since they must intercalate through the crystal layers. In our previous study, we reported that the [0001]-oriented PbI 2 nanowires show three-fold symmetric sidewalls (i.e., truncated hexagons), which are primarily comprised of {1010}-type facets [33]. In accordance with this knowledge, we note that the type A nanowires observed in this work generally exhibited "tapered oscillatory" morphology, suggesting that the original {1010} sidewalls are multi-faceted into other planes [49].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Thus, the difference in the degree of perovskite conversion between type A and B might be related to the accessibility of gaseous MAI onto the surface of nanowire sidewalls, necessitating the evaluation of MAI affinity to the exposed PbI 2 surface facets since they must intercalate through the crystal layers. In our previous study, we reported that the [0001]-oriented PbI 2 nanowires show three-fold symmetric sidewalls (i.e., truncated hexagons), which are primarily comprised of {1010}-type facets [33]. In accordance with this knowledge, we note that the type A nanowires observed in this work generally exhibited "tapered oscillatory" morphology, suggesting that the original {1010} sidewalls are multi-faceted into other planes [49].…”
Section: Resultssupporting
confidence: 88%
“…Anisotropic van der Waals layered semiconductors, such as germanium (II) sulfide were also demonstrated to grow via VLS mechanism, as reported by Sutter et al [30]. Our previous study showed that lead iodide (PbI 2 ), another van der Waals type material system, can homoepitaxially grow on the PbI 2 substrate layers pre-deposited on the muscovite mica surface [33]. These results emphasize the VLS mechanism as a universal approach to fabricate intrinsically two-dimensional van der Waals type crystals into one-dimensional nanowire structures, which may open up the new methodology to modulate their physical properties.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations